Qualitative Development of Construction Student’s Attitude in Ecological Teaching and Learning Process - Bērziņš, Andris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The publication reflects the qualitative development of construction students' ecological attitude in learning and teaching process in a vocational school. By facilitating the teaching and learning process, developing the content of education, introducing in teaching ecologically-oriented forms of work, methods, approaches and instruments; using the environment as a pedagogical tool and highlighting the important role of teacher as an ecological person in the accentuation of teaching content as students understand it. The author emphasizes the impact of the components of ecological education in the promotion of the reflection on the most essential attitude criteria – knowledge, skills and behaviour. Applying quantitative and qualitative research, the author sums up the experimantally obtained results showing that by the introduction of the components of ecological education, it is possible to foster the development of an ecological person.